Concomitant aortic root replacement during frozen elephant trunk implantation does not increase perioperative risk. (20th February 2023) - Berger, Tim; Chikvatia, Salome; Siepe, Matthias; Kondov, Stoyan; Meissl, Dominic; Gottardi, Roman; Rylski, Bartosz; Czerny, Martin; Kreibich, Maximilian
Abstract: OBJECTIVES: Our aim was to evaluate the risk of concomitant aortic root replacement during frozen elephant trunk (FET) total arch replacement. METHODS: Between March 2013 and February 2021, 303 patients underwent aortic arch replacement using the FET technique. Patient characteristics, intra- and postoperative data were compared between patients with ( n = 50) and without ( n = 253) concomitant aortic root replacement (implantation of a valved conduit or using the reimplantation valve-sparing technique) after propensity score matching. RESULTS: After propensity score matching, there were no statistically significant differences in preoperative characteristics including the underlying pathology. There was no statistically significant difference regarding arterial inflow-cannulation or concomitant cardiac procedures, while cardiopulmonary bypass ( P < 0.001) and aortic cross-clamp ( P < 0.001) times were significantly longer in the root replacement group. Postoperative outcome was similar between the groups and there were no proximal reoperations in the root replacement group during follow-up. Root replacement was not predictive for mortality ( P = 0.133, odds ratio: 0.291) in our Cox regression model. There was no statistically significant difference in overall survival (log rank: P = 0.062). CONCLUSIONS: Concomitant FET implantation and aortic root replacement prolongs operative times but does not influence postoperative outcomes or increase operative risk in an experienced high-volume centre. The FET procedure did not appear to be a contraindication for concomitant aortic root replacement even in patients with borderline indications for aortic root replacement. Abstract : The frozen elephant trunk (FET) procedure has evolved as an effective and common treatment in patients with thoracic aortic pathologies involving the aortic arch with good postoperative outcome but a high incidence of planned and unplanned distal aortic reinterventions [1–7].